NK Cell Activation in Human Hantavirus Infection Explained by Virus-Induced IL-15/IL15Rα Expression - Braun, Monika (PLoS Pathog, 2014)
Clinical infection with hantaviruses cause two severe acute diseases, hemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS). These diseases are characterized by strong immune activation, increased vascular permeability, and up to 50% case-fatality rates. One prominent feature observed in clinical hantavirus infection is rapid expansion of natural killer (NK) cells in peripheral blood of affected individuals. We here describe an unusually high state of activation of such expanding NK cells in the acute phase of clinical Puumala hantavirus infection. Expanding NK cells expressed markedly increased levels of activating NK cell receptors and cytotoxic effector molecules. In search for possible mechanisms behind this NK cell activation, we observed virus-induced IL-15 and IL-15Rα on infected endothelial and epithelial cells. Hantavirus-infected cells were shown to strongly activate NK cells in a cell-cell contact-dependent way, and this response was blocked with anti-IL-15 antibodies. Surprisingly, the strength of the IL-15-dependent NK cell response was such that it led to killing of uninfected endothelial cells despite expression of normal levels of HLA class I. In contrast, hantavirus-infected cells were resistant to NK cell lysis, due to a combination of virus-induced increase in HLA class I expression levels and hantavirus-mediated inhibition of apoptosis induction. In summary, we here describe a possible mechanism explaining the massive NK cell activation and proliferation observed in HFRS patients caused by Puumala hantavirus infection. The results add further insights into mechanisms behind the immunopathogenesis of hantavirus infections in humans and identify new possible targets for intervention.